Genome-wide analysis and functional characterization of the SUT gene family associated with stress tolerance in Glycine max - Cui, Tianyi; He, Rong; Wang, Pengwei; Zhu, Zhen; Xing, Han; Zhao, Jinming; Guo, Na (Frontiers in Plant Science, 2026)
BackgroundSoybean (Glycine max), is a globally important oilseed crop whose yield and quality are severely constrained by environmental stress. The Sucrose Transporter (SUT) gene family plays a crucial role in sucrose transport, plant growth, and stress adaptation. However, comprehensive identification and functional characterization of SUT family members in soybean remain largely incomplete.ResultsIn this study, a total of 12 non-redundant GmSUT genes were identified in soybean. The encoded proteins have predicted molecular weights ranging from 11.80 to 65.88 kDa and theoretical isoelectric points (pI) between 5.73 and 9.44. These genes were classified into three subfamilies (SUTI, SUTIIa and SUTIV) by phylogenetic analysis, with SUTI being the largest group. Gene structure and conserved motif analyses showed that motif composition was largely uniform within each subfamily, except for GmSUT4.1, which retained only two motifs. Chromosomal mapping revealed an uneven distribution across seven chromosomes, with Chr16 harboring four SUTI members. Collinearity analysis indicated a closer evolutionary relationship between soybean and Glycine soja than with Arabidopsis thaliana or Medicago truncatula. Cis −regulatory element analysis identified abundant stress- and hormone-responsive motifs (e.g., ABRE, MeJA−responsive elements), with 83% of promoters containing ABA-responsive elements. Moreover, the transcriptional levels of the GmSUT genes were significantly induced under various abiotic stresses (salt, drought, cold and alkaline) and phytohormone treatments (ABA, and MeJA), demonstrating that multiple GmSUT genes play critical roles in soybean stress adaptation.ConclusionsThis study provides a comprehensive identification and characterization of the SUT gene family in soybean (Glycine max), revealing 12 GmSUT genes grouped into three subfamilies (SUTI, SUTIIa, SUTIIV). Expression profiling demonstrated that multiple GmSUT members are rapidly upregulated under stress treatment, underscoring their essential functions in sucrose distribution and stress adaptation. These findings offer valuable insights into the regulatory mechanisms of the GmSUT family and suggest candidate genetic targets for enhancing stress tolerance in soybean.